Interrelationships of brain location, parents’ trait anxiety, sex and trait anxiety among anxious children in Kuala Lumpur, Malaysia - Cheong, Chen Chen (2021)
Over recent year, the prevalence rate of anxiety had increased consistently. Existing research recognizes the critical role played by the biological attributions of risk factors for anxiety as it had formed the first anxious personality of trait anxiety since childhood. However, the increased prevalence rate for anxiety disorder remains unresolved and some of the biological attributed risk factors remained unidentified. Therefore, the study aims to study the relationships between brain location, parents’ trait anxiety and sex with trait anxiety among anxious Chinese children in Kuala Lumpur. A cross-sectional study using convenient sampling was carried out among 212 Chinese children aged between age eight to 13 years old with high trait anxiety. Data for this study were collected using self-administered State-Trait Anxiety Inventory for Children-Trait Scale (STAIC-T) and State-Trait Anxiety Inventory-Trait Scale (STAI-T) to measure the trait anxiety score for children and parents respectively. Besides, an objective measurement of brain electrical activity with Electroencephalogram (qEEG) brain mapping were adopted to identify the associated brain locations quantitatively according to International 10-20 System. Data analysis was conducted using IBM Version 2.0 Statistical Package for the Social Sciences (SPSS) which involved descriptive and inferential statistical analyses. Results showed that there was a significant relationship between all the locations at prefrontal cortex (Fp1, Fp2, F7, F8, F3, F4) and temporal lobe (T3, T4) with trait anxiety among children. Specifically, brain location F8 was the unique predictor for trait anxiety among children. Besides, results showed that there was a significant positive relationship between parents’ trait anxiety level with children’s trait anxiety level. In term of sex, there was a mean difference in trait anxiety level with females showed higher trait anxiety level. Findings from present study revealed that brain location, parents’ trait anxiety and sex played a role in affecting the trait anxiety level of individual since born. Findings from this research highlighted that identification of biological vulnerability among children could provide inputs which can assist in designing preventative action and early intervention to reduce the trait anxiety among Chinese children in Kuala Lumpur.